2014
DOI: 10.1142/s0219581x14500100
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis and Characterization of Silver Nanoparticles for Antimicrobial Activity Against Burn Wounds Contaminating Bacteria

Abstract: Silver nanoparticles ( AgNPs ) were prepared from the plant extract of N. arbor-tristis under atmospheric conditions through green synthesis and characterized by various physicochemical techniques like UV-Visible spectroscopy, IR Spectra, energy dispersive X-ray spectrometry (EDS), X-ray diffraction and transmission electron microscopy (TEM) and the results confirmed the synthesis of homogeneous and stable AgNPs by the plant extracts. The antimicrobial activity of AgNPs was investigated against most common bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The ethanol precipitated, N. arbor-tristis extract-synthesized Ag nanostructure is confirmed by the characteristic diffraction peaks observed at the 2θ angles 38.06°, 44.24°, 64.58° and 77.38° in the XRD pattern (Figure 2). These peaks are indexed as (111), (200), (220), and (311) respectively, and their crystallographic planes correspond to the characteristic face-centered cubic (fcc) silver lines in accordance with the study of Rout et al [52], a value in good agreement with the powder data of JCPDS Card number 04-0783.…”
Section: X-ray Diffraction Analysis Of Ag Npssupporting
confidence: 85%
See 1 more Smart Citation
“…The ethanol precipitated, N. arbor-tristis extract-synthesized Ag nanostructure is confirmed by the characteristic diffraction peaks observed at the 2θ angles 38.06°, 44.24°, 64.58° and 77.38° in the XRD pattern (Figure 2). These peaks are indexed as (111), (200), (220), and (311) respectively, and their crystallographic planes correspond to the characteristic face-centered cubic (fcc) silver lines in accordance with the study of Rout et al [52], a value in good agreement with the powder data of JCPDS Card number 04-0783.…”
Section: X-ray Diffraction Analysis Of Ag Npssupporting
confidence: 85%
“…Rout et al, also biosynthesized Ag NPs using a leaf extract of N. arbor-tristis with an average size of 20 nm. [52] However, their TEM study used the crude Ag NP colloidal solution without separation or purification, which known to affect the particle size.…”
Section: Introductionmentioning
confidence: 99%
“…Juss., 69 Arnebia nobilis Rech.f., 70 Melia dubia Cav., 71 Terminalia chebula Retz., 72 Lansium domesticum Corrêa, 73 Orchidantha chinensis T.L.Wu, 74 A. vera (L.) Burm.f., 75 glucuronoxylan, 76 Momordica charantia L., 77,78 Carica papaya L., 79 Cymbopogon citratus (DC.) Stapf, 80 Nyctanthes arbor-tristis L., 81 Naringi crenulata (Roxb.) Nicolson, 82 Phytophthora infestans, 83 Biophytum sensitivum, 84 Propolis, 85 and Bryonia laciniosa L. 86 Most of these extracts possess inherent antibacterial and antimicrobial activity, which makes them appropriate for wound care.…”
Section: Green-synthesized Metal Nanoparticles Using Plantsmentioning
confidence: 99%
“…After 0 minute of reaction of the yellow colour mixture of AgNO 3 solution with leaf extract was changed black suspended mixture very rapidly at room temperature just after 2 minutes. It was observed that the biosynthesis of SNPs using leaf extracts of Ocimum sanctum was taken place very rapidly than the other plants leaf [39]. The leaf extracts of Ocimum sanctum and concentrations of AgNO 3 solution were also wide-ranging at 5% to 10% and 1 to 4 mM by volume, respectively.…”
Section: Synthesis Of Silver Nanoparticles (Snps)mentioning
confidence: 99%